Charge collection from within a collecting junction well - Kurniawan, Oka. (2010)
This paper provides the analytical equation for the charge collection from a collecting region with a finite dimension. Electron-beam-induced current has widely been used for semiconductor characterization. The availability of analytical expressions would further enhance the study and development of various measurement techniques. Nevertheless, most devices are fabricated with junctions that have finite dimensions, which are usually either L shaped or U shaped. For these cases, the analytical expressions are lacking. This paper provides the derivation of the electric current profile when an electron beam scans from within the collecting region for these two cases. The computation was